Implementation of business process reengineering (BPR): Case study of official trip procedures in higher education institutions - Rina Djunita Pasaribu; Grisna Anggadwita; Ratih Hendayani; Raswyshnoe Boing Kotjoprayudi; Dessy Indah Nur Apiani (Journal of Industrial Engineering and Management (JIEM), 2021)
Purpose: Official trip is one of the common business processes carried out by every organization, including educational institutions. However, in its implementation, there are various kinds of obstacles that have an impact on the lack of effectiveness and efficiency of the system, in terms of time, material and human resources. This study aims to evaluate existing business processes and design, and implement the results of business process re-engineering (BPR) in the official trip system which is supported by digitization and digitalization with a multi-unit integration approach at one of the private universities in Indonesia, Telkom University. Design/methodology/approach: This study uses a mixed-method with an embedded design approach. The quantitative method was carried out by calculating the performance of official trip procedures before and after the BPR. Meanwhile, the qualitative method was carried out by conducting interviews and Focus Group Discussions (FGD) with key informants in this study. Triangulation technique was used to validate the research results. Findings: The BPR process has resulted in radical changes to the official trip system at the university, namely from a mixed system of manual / offline & online to completely online, from a very centralized to decentralized decision process, and the availability of a transparent monitoring system. These changes provide significant results by increasing the effectiveness and efficiency of business processes so as to speed up time, save paper (reduce paper waste and reduce costs) and optimize employee assignments. Originality/value: This study adds new insights into the implementation of BPR to the official trip system in higher education. This research implies that BPR can produce radical changes in business processes in higher education to become more effective and efficient. In addition, this study proposes several practical and academically useful recommendations for further research in this area.
Keywords: 650; BPR; digitalization; digitization; industry 4.0; official trip; online SPPD; higher education